Bergenin attenuates neuropathic pain by modulation of TRPV1/CGRP signalling and neuro-inflammatory mechanisms - Anmol; Anagha Gadepalli; Akhilesh Kotiyal; Deepak Chouhan; Dilip Sharma; Vinod Tiwari (Molecular Biology Reports, 2026)

Expectations versus reality: flood-driven microplastic distribution in water and sediments of the Arno River (Italy) - Francesca Uguagliati; Anmol Raj Mandal; Marta Baccarin; Massimiliano Zattin; Massimiliano Ghinassi (Environmental Pollution, 2026)

Life-cycle and techno-economic analyses of agro-waste-derived biodegradable plastics enhanced via AI-based parametric optimization - Abhishek Kumar Singh; Md Monjurul Islam; Parul Sharma; Anmol Sharma; Sankha Chakrabortty; Riti Kumari; Sayantan Sarkar; Moonis Ali Khan; Ramesh Kumar; Byong-Hun Jeon (Environmental Research, 2026)

IRP1 deficiency promotes fibroblast activation through iron dysregulation: protective modulation by H2S - Anmol Bola; Alex McFadden; Oyine Favour Ochigbo; Hassan Mustafa Arif; Rui Wang; Kostas Pantopoulos; Guangdong Yang (Molecular and Cellular Biochemistry, 2026)

s40Ar/39Ar geochronology and geochemistry of the Vikramgad-Murbad tholeiitic dyke swarm, Deccan traps: Understanding the feeder dyke system of the Western Ghats flood basalt sequence - B. Astha; Hetu Sheth; Hijas Hameed; Anmol Naik; Waliur Rahaman; Hugo K.H. Olierook; Fred Jourdan; Christopher L. Kirkland; Arunodaya Shekhar (Geochemistry, 2026)

Spatiotemporal simulation of mining-induced land-use transitions and impacts of early eco-rehabilitation on carbon dynamics across the mineral rich landscape, India - Prashant Sharma; Shibnarayan Pratihar; Bitan Goswami; Farkhanda Jabeen; Anmol Namrata Gupta; Aman Kumar Sinha; Bablee Kumari Singh; Munegowda Manoj Gowda; Anshuman Das; Shambhu Nath Mishra; Yogeshwar Mishra; Rajiv Pandey (Environmental Research, 2026)

Design Development and Optimization Using Box-Behnken Design (BBD) and in Vitro Evaluation of Cromolyn-Loaded Niosomes for Management of Alzheimer’s Disease - Anmol Kanda; Anjna Rani (Journal of Pharmaceutical Innovation, 2026)

Development and Therapeutic Evaluation of a Dual-loaded Glycerosomal Gel of Quercetin and Resveratrol in an Arthritic Rat Model - Jyotsna Kharbanda; Rupa Mazumder; Anmol Dogra; Neelam Singh; Rakhi Mishra (Journal of Pharmaceutical Innovation, 2026)

Elwendia persica (Boiss.) Pimenov & Kljuykov from Indian Western Himalaya: impact of geographical locations on essential oil yield, chemical diversity, anti-bacterial, anti-diabetic and anti-oxidant activities - Gaurav Aggarwal; Anmol; Subhash Kumar; Vivesh Sood; Dharam Singh; Amit Chawla; Mohit Sharma; Upendra Sharma (Natural Product Research, 2026)

A review of phytochemicals targeting bacterial biofilm and quorum sensing pathways: molecular, microbiological, and mechanistic insights - Anmol Srivastava; Nidhi Verma; Roopal Gupta; Vishnu Agarwal (Archives of Microbiology, 2026)

Too Many Bones to Pick - from Overproduction to Refinement: Evidence for Trabecular Pruning in Early Postnatal Development as a Distinct Phase of Skeletal Functional Adaptation - Meir M. Barak; Anmol Madaan; Jack Nguyen; Sarah Borgel Francis (Annals of Biomedical Engineering, 2026)

Invisible gold mineralization within the Vempalle Dolostone, Joolakalva Area, Cuddapah Basin, Southern India: Insights from in-situ and whole-rock geochemistry - Ramesh Chandra Behera; Sahendra Singh; Anmol Barla; K.S. Vijay Kumar; N. Ramakrishna Reddy; Mahimaa Dash (Lithos, 2026)

Inferring the magma injection sequence in ancient multiple dykes based on geochemical variations: the Kinhavli dyke, Deccan Traps, India - B. Astha; Hetu Sheth; Anmol Naik; Ghulam Rabbani; Waliur Rahaman; Arunodaya Shekhar (Journal of Volcanology and Geothermal Research, 2026)

Understanding the Impact of Endocrine Disrupting Chemicals (EDCs) and Mechanisms of Microbial Biodegradation: A Review - Anmol Kaur; Rupshikha Patowary (Water, Air, & Soil Pollution, 2026)

Improved virtual point source formulation for continuous atmospheric release of pollutant from a volume source - Manish Chopra; R B Oza; R Shrivastava; Indumathi S Iyer; Anmol Batra (Journal of Earth System Science, 2026)

Anti-quorum, anti biofilm activity of FDA approved drugs against P. aeruginosa: in silico and in vitro studies - Vivek Kumar; Anmol Srivastava; Vishnu Agarwal (Biotechnology Letters, 2026)

Investigating the bioactive phytoconstituents of Cocculus hirsutus (L.) W.Theob.: UHPLC-PDA-based quantification, UHPLC-Q-TOF-MS/MS-based qualitative analysis and network pharmacology-based target prediction - Shivani; Anmol; Shiv Kumar; Prateek Singh Bora; Upendra Sharma (South African Journal of Botany, 2026)

Petrological and volcanological evolution of the Gandhi Tekdi vitrophyre: A late-stage silicic lava dome in the western Deccan continental flood basalt province - Arunodaya Shekhar; Hetu Sheth; B. Astha; Anmol Naik; Waliur Rahaman; Subham Kumar (Lithos, 2026)

Rainfall extremes variability, teleconnections with atmospheric circulation anomalies in the Indian summer monsoon - Anmol Yadav; G.P. Singh; Pradeep Kumar Rai; Vijay Kumar Soni; Akhilesh Mishra; Sonu Kumar (Dynamics of Atmospheres and Oceans, 2026)

Explicit consideration of human exposure to minimize freight routing impacts - Sarah Dennis-Bauer; Anmol Pahwa; Miguel Jaller (Transportation Research Part D: Transport and Environment, 2026)

A benchmark UPLC-based method for concurrent analysis of seventeen Stevia rebaudiana metabolites (steviol, isosteviol, and fifteen steviol glycosides) in a single analytical run and its implementation in diverse products - Pawan Kumar; Anmol; Sahil Awasthi; Rajiv Kumar Tonk; Mohit Sharma; Upendra Sharma (Food Research International, 2026)

Sodium carbonate and sodium chloride as elicitors of secondary metabolite production in callus cultures of Fagonia indica - Muhammad Uzair Javed; Muhammad Asad Ullah; Tehreem Mahmood; Taimoor Khan; Iva Viehmannova; Anmol Akbar; Yasir Khan; Tariq Khan; Bilal Haider Abbasi; Christophe Hano; Nathalie Giglioli-Guivarc’h (Plant Biosystems, 2026)

Interflow and intraflow boles, and potential pitfalls in bole-based geology and stratigraphy of continental flood basalts - Hetu Sheth; Anmol Naik; Janisar M. Sheikh; Alok Kumar (Journal of Volcanology and Geothermal Research, 2026)

Investigating the pesticidal efficacy of actinobacteria species against Sitophilus oryzae and Tribolium confusum - Syed Khalida Izhar; Shareen Fatima Rizvi; Anmol Gupta; Ahmed Alafnan; Saba Siddiqui; Uzma Shahab; Irfan Ahmad; Saheem Ahmad; Uzma Afaq (Journal of Stored Products Research, 2026)

An assessment of grazing associated elevation of heat stress during hot humid summer in sedentary and migratory goat breeds of Jammu region - Anmol Pareek; Vaishali Sharma; Asma Khan; Dipanjali Konwar; Biswajit Brahma (Tropical Animal Health and Production, 2026)

Targeting Microbial Biofilms and Promoting Wound Healing in MRSA-Infected Diabetic Rats using Postbiotics of Lactiplantibacillus plantarum - Anmol Narang; Kirandeep Kaur; Neena Bedi; Neha Rajput; Gagandeep Kaur; Sukhraj Kaur (Probiotics and Antimicrobial Proteins, 2026)

A Review on Structural Insights into NLRP3 and NEK7: Domain Architecture, Subcellular Localization, and Their Interaction in Inflammasome Assembly and Signaling - Anmol Sood (Molecular Neurobiology, 2026)

Ozone enhances biological treatment of hydrothermal liquefaction aqueous stream from municipal sludge - Anmol Parajuli; Cigdem Eskicioglu (Bioresource Technology, 2025)

Acute Pre- and Post-administration of Lactiplantibacillus plantarum 2034 and Its Secretory Metabolites Ameliorates Hyperglycaemia, Hyperlipidaemia, and Oxidative Stress in Diabetic Rats - Anmol Narang; Muzamil Rashid; Shubham Thakur; Subheet Kumar Jain; Amarjeet Kaur; Sukhraj Kaur (Probiotics and Antimicrobial Proteins, 2025)

Polymeric Microspheres for Sustained Delivery of Rutin in the Management of PCOS - Monalisa Roy; Rupa Mazumder; Neelam Singh; Anmol Dogra; Rakhi Mishra (Journal of Pharmaceutical Innovation, 2025)

Thio-Functionalized β-Cyclodextrin as a Metal-Binding Therapeutic Scaffold: Coordination with Co (II)/Cu (II), Antibacterial Activity, and in Silico Evaluation for Biomedical Use - Pritika Gurung; Sudarshan Pradhan; Anmol Chettri; Sudeshna Nandi; Tanmoy Dutta; Malay Bhattacharya; Biswajit Sinha (Journal of Fluorescence, 2025)

Genetic variability for yield attributes and blast disease in pearl millet [Pennisetum glaucum (L.) R. Br.] germplasm - Dilbagh; Sagar; Anand Kumar; Rutuparna Pati; Anmol Sandhu; K. D. sehrawat; Sanjay Kumar Sanadya; Prashant Kaushik; Daya Shankar Mishra (Vegetos, 2025)

A new sesquiterpenoid from the roots of Nardostachys jatamansi (D.Don) DC - Mehak Sharma; Anmol; Upendra Sharma (Natural Product Research, 2025)

Ammonia and organic carbon transformation in autogenic continuous flow supercritical water oxidation reactor - Jianna Li; Conrad Austin; Stuart Moore; Anmol Purohit; Shuzhong Wang; Jun Hu; Nizette Consolazio; John C. Kramlich; Igor V. Novosselov (Journal of Environmental Chemical Engineering, 2025)

Unveiling molecular signatures for precision drug design: machine learning insights from trypanothione reductase, PKC-θ, and CB1 - Sunil Sahu; Adarsh Anmol; Tushar Nishad; Satya Eswari Jujjavarapu (Molecular Diversity, 2025)

Behavior of fiber-reinforced concrete (FRC) columns reinforced with longitudinal hybrid (Steel/GFRP) reinforcement and GFRP crossties and spirals under reversed lateral cyclic loading - Anmol Shanker Srivastava; Girish Narayan Prajapati; Brahim Benmokrane (Engineering Structures, 2025)

Calcium Dynamics in Strawberry (Fragaria x ananassa Duch.) Plant: from Soil to Fruit - Sudhanshu Singh; Akash Kumar; Niharika Thakur; Avantika Bisht; Anmol; Shailesh Kumar Singh; Manish Bakshi (Journal of Soil Science and Plant Nutrition, 2025)

Interstitial silicic glasses in the Vikramgad-Murbad tholeiitic dyke swarm, Konkan Plain, western Deccan Traps: implications for silicic magma genesis in continental flood basalt provinces - B. Astha; Hetu Sheth; Anmol Naik; Arunodaya Shekhar (Contributions to Mineralogy and Petrology, 2025)

Efficacy of natural deep eutectic solvents for extracting isoquinoline alkaloids of plant origin: A case study with Cissampelos pareira L. - Surekha Kumari; Anmol; Shivani; Upendra Sharma (South African Journal of Botany, 2025)

Magnetite nanoparticles loaded onto inexpensive candle soot particles as a promising material for the elimination of potentially toxic aqueous methylene blue and crystal violet dye molecules - Anmol Pandey; Ashish Bhagat; Bhaskar Bhaduri (Journal of Environmental Chemical Engineering, 2025)

Translational paradigm in nanodiagnostics applications of functionalized zinc oxide nanoforms interface for pathogenic virus diagnostics - Abha Gupta; Apoorv Kirti; Rudra Narayan Sahu; Sudakshya S. Lenka; Anu Yadav; Anmol Choudhury; Adrija Sinha; Aditya Nandi; Nirmal Kumar Mohakud; Swadheena Patro; Aishee Ghosh; Nagendra Kumar Kaushik; et al. (Chemical Engineering Journal, 2025)

Interconnections of screen time with neuroinflammation - Ashish Verma; Anmol Kumar; Satendra Chauhan; Nisha Sharma; Anuradha Kalani; Prakash Chandra Gupta (Molecular and Cellular Biochemistry, 2025)

Modulating Productivity of Strawberries (Fragaria x ananassa Duch.) Through Artificial Full-Spectrum Light in Indoor Vertical Farming - Pallvi Verma; Gurpreet Singh; Shailesh Kumar Singh; Anis Ahmad Mirza; Manish Bakshi; Anmol; Lakshya; Lokesh Kumar; Rupesh (Journal of Soil Science and Plant Nutrition, 2025)

Regeneration of PFAS-laden granular activated carbon by modified supercritical CO2 extraction - Tatiana Didenko; Almond Lau; Anmol L. Purohit; Ji Feng; Brian Pinkard; Mohamed Ateia; Igor V. Novosselov (Chemosphere, 2025)

Fabrication, characterization and flocculation properties of starch, chitosan or cellulose based graft copolymers: A review - Shubhangi Pandey; Anmol Kumar; Krishna Kumar; S. Krishnamoorthi; Kranthikumar Tungala (Bioresource Technology Reports, 2025)

Automated masonry spalling severity segmentation in historic railway tunnels using deep learning and a block face plane fitting approach - Jack Smith; Chrysothemis Paraskevopoulou; Anthony G. Cohn; Ryan Kromer; Anmol Bedi; Marco Invernici (Tunnelling and Underground Space Technology, 2024)

Controlled in vivo intrinsic detrimental effect of d-Limonene channelized by influential proximal interaction through apoptosis and steatosis in embryonic zebrafish (Danio rerio) - Anmol Choudhury; Sudakshya S. Lenka; Abha Gupta; Deepa Mandal; Adrija Sinha; Utsa Saha; Shaikh Sheeran Naser; Dibyangshee Singh; Faizan Zarreen Simnani; Aishee Ghosh; Shalini Kumari; Apoorv Kirti; et al. (Science of The Total Environment, 2024)

Chemical Composition and Insecticidal Potential of Essential Oil from Murraya koenigii (L.) Obtained by Natural Deep Eutectic Solvents - Mehak Sharma; Urvashi; Himanshi Gupta; Anmol; Upendra Sharma; S. G. Eswara Reddy (Neotropical Entomology, 2024)

Lignification based screening of pea (Pisum sativum L.) germplasm for resistance to rust (Uromyces viciae–fabae) - Anmol Singh Yadav; Shyam Saran Vaish; Anil Kumar Singh; Ramesh Chand (Journal of Plant Pathology, 2024)

Exploring phenolic compounds as natural stress alleviators in plants- a comprehensive review - Nancy Saini; Anmol Anmol; Sanjeev Kumar; Ab Waheed Wani; Manish Bakshi; Zarina Dhiman (Physiological and Molecular Plant Pathology, 2024)

Pollination deficit in apples increases with elevation - Ann M. Fraser; Ginger R.H. Allington; Aman Luthra; Preeti Virkar; Shweta Rana; Renu Suyal; Ankita Rawat; Anmol Ratna; Kiran Cunningham; Narendra Raikwal; Anvita Pandey; Vishal Singh (Agriculture, Ecosystems & Environment, 2024)

Cadmium toxicity: its’ uptake and retaliation by plant defence system and ja signaling - Shruti Kaushik; Alok Ranjan; Anmol Sidhu; Anil Kumar Singh; Geetika Sirhindi (BioMetals, 2024)

An In-Silico Drug Designing Approach Attempted on a Newly Synthesized Co(II) Complex along with its Other Biological Activities: A Combined Investigation of both Experimental and Theoretical Aspects - Sudarshan Pradhan; Dipu Kumar Mishra; Pritika Gurung; Anmol Chettri; Uttam Kumar Singha; Tanmoy Dutta; Biswajit Sinha (Journal of Fluorescence, 2024)

Selenium levels in colorectal cancer: A systematic review and meta-analysis of serum, plasma, and colorectal specimens - Amit Pal; Aninda Dhar; Muhammad Aaqib Shamim; Isha Rani; Ram Rattan Negi; Aaina Sharma; Namrata Chatterjee; Anmol Goyal; Sadashiv; Bandhan Kaur; Vincenzo Tondolo; Mauro Rongioletti; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Lava squeeze-ups and volcanic resurfacing: a review - Hetu Sheth; Anmol Naik; Arunodaya Shekhar; B. Astha; Hrishikesh Samant (Journal of Volcanology and Geothermal Research, 2024)

Evaluation of antiplasmodial potential of Cissampelos pareira L.: Characterization and quantification of isoquinoline alkaloids responsible for the biological activity - Surekha Kumari; Anmol; Shivani; Prakhar Agrawal; Dinkar Sahal; Upendra Sharma (South African Journal of Botany, 2024)

Evaluating private and system-wide impacts of freight eco-routing - Anmol Pahwa; Miguel Jaller (Transportation Research Part D: Transport and Environment, 2024)

Biofilm inhibition/eradication: exploring strategies and confronting challenges in combatting biofilm - Anmol Srivastava; Nidhi Verma; Vivek Kumar; Pragati Apoorva; Vishnu Agarwal (Archives of Microbiology, 2024)

Synthesis and Characterization of Zn(II) Complex of 4-chloro-2-(((2-phenoxyphenyl)imino)methyl)phenol and its Biological Efficacies: DNA Interaction, ADMET, DFT and Molecular Docking Study - Uttam Kumar Singha; Sudarshan Pradhan; Pritika Gurung; Prajal Chhetri; Anmol Chettri; Tanmoy Dutta; Biswajit Sinha (Journal of Fluorescence, 2024)

Synthesis of Novel [{(2-Amino-5-Nitro-N-[(E)-Thiophen-2-yl-Methylidene]Aniline-κ3N1:N4:S)(Sulphato-κ2O1:O3)}Zinc(II)] Complex with Physico-Chemical and Biological Perspective Exploration: A Combined Experimental and Computational Studies - Sudarshan Pradhan; Pritika Gurung; Anmol Chettri; Uttam Kumar Singha; Prajal Chhetri; Tanmoy Dutta; Biswajit Sinha (Journal of Fluorescence, 2024)

A cularine-type isoquinoline alkaloid from the root part of Cissampelos pareira - Surekha Kumari; Anmol; Upendra Sharma (Natural Product Research, 2024)

Mefenamic Acid Loaded and TPGS Stabilized Mucoadhesive Nanoemulsion for the Treatment of Alzheimer’s Disease: Development, Optimization, and Brain-Targeted Delivery via Olfactory Pathway - Anmol Dogra; Ramandeep Singh Narang; Tajpreet Kaur; Jasjeet Kaur Narang (AAPS PharmSciTech, 2024)

Cyperus rotundus L.: Invasive weed plant with insecticidal potential against Aphis craccivora Koch and Planococcus lilacinus (Cockerell) - Raman Singh; Himanshi Gupta; Anmol; Gaurav Aggarwal; Kangkanjyoti Bhattacharyya; Upendra Sharma; S.G. Eswara Reddy (Pesticide Biochemistry and Physiology, 2024)

NADES-based selective extraction of bioactive molecules: A case study with commercially important Himalayan medicinal plant Aconitum heterophyllum - Anmol; Mehak Sharma; Patil Shivprasad Suresh; Shiv Shankar Gupta; Upendra Sharma (Sustainable Chemistry and Pharmacy, 2023)

Predictors of disease severity in COVID-19 associated mucormycosis: impact of HbA1C levels, time lag to mucormycosis onset, and radiologic patterns of paranasal sinuses and spaces involvement - Prajwal Rao; Varsha Rangankar; Shalesh Rohatgi; Prashant Dubey; Advait Gitay; Anmol Singh; S.L Jadhav; Satish Nirhale; Pravin Naphade (Infectious Diseases, 2023)

Estimating last-mile deliveries and shopping travel emissions by 2050 - Miguel Jaller; Runhua (Ivan) Xiao; Sarah Dennis-Bauer; Daniel Rivera-Royero; Anmol Pahwa (Transportation Research Part D: Transport and Environment, 2023)

Functional network disorganization and cognitive decline following fractionated whole-brain radiation in mice - Benjamin A. Seitzman; Francisco J. Reynoso; Timothy J. Mitchell; Annie R. Bice; Anmol Jarang; Xiaodan Wang; Cedric Mpoy; Lori Strong; Buck E. Rogers; Carla M. Yuede; Joshua B. Rubin; Stephanie M. Perkins; et al. (GeroScience, 2023)
Cognitive dysfunction following radiotherapy (RT) is one of the most common complications associated with RT delivered to the brain, but the precise mechanisms behind this dysfunction are not well understood, and to date, there are no preventative measures or effective treatments. To improve patient outcomes, a better understanding of the effects of radiation on the brain’s functional systems is required. Functional magnetic resonance imaging (fMRI) has shown promise in this regard, however, compared to neural activity, hemodynamic measures of brain function are slow and indirect. Understanding how RT acutely and chronically affects functional brain organization requires more direct examination of temporally evolving neural dynamics as they relate to cerebral hemodynamics for bridging with human studies. In order to adequately study the underlying mechanisms of RT-induced cognitive dysfunction, the development of clinically mimetic RT protocols in animal models is needed. To address these challenges, we developed a fractionated whole-brain RT protocol (3Gy/day for 10 days) and applied longitudinal wide field optical imaging (WFOI) of neural and hemodynamic brain activity at 1, 2, and 3 months post RT. At each time point, mice were subject to repeated behavioral testing across a variety of sensorimotor and cognitive domains. Disruptions in cortical neuronal and hemodynamic activity observed 1 month post RT were significantly worsened by 3 months. While broad changes were observed in functional brain organization post RT, brain regions most impacted by RT occurred within those overlapping with the mouse default mode network and other association areas similar to prior reports in human subjects. Further, significant cognitive deficits were observed following tests of novel object investigation and responses to auditory and contextual cues after fear conditioning. Our results fill a much-needed gap in understanding the effects of whole-brain RT on systems level brain organization and how RT affects neuronal versus hemodynamic signaling in the cortex. Having established a clinically-relevant injury model, future studies can examine therapeutic interventions designed to reduce neuroinflammation-based injury following RT. Given the overlap of sequelae that occur following RT with and without chemotherapy, these tools can also be easily incorporated to examine chemotherapy-related cognitive impairment.

Basaltic thermal and material inputs in rhyolite petrogenesis: the Chhapariyali rhyolite dyke, Saurashtra, Deccan Traps - Janisar M. Sheikh; Ciro Cucciniello; Anmol Naik; Hetu Sheth; Raymond Duraiswami (Geochemistry, 2023)

Fate of 1,3-dioxolane in the troposphere: kinetics, mechanism with theoretical support, and atmospheric implications - Anmol Virmani; Mohini P. Walavalkar; Asmita Sharma; Ankur Saha; Sumana Sengupta; Awadhesh Kumar (Journal of Atmospheric Chemistry, 2023)

Experimental and numerical investigation on structural bolts under compression - Md Kamrul Hassan; Bulbul Ahmed; Anmol Ram; Mohamed Ghannam; Swapan Saha (Innovative Infrastructure Solutions, 2023)

Combating polymicrobial biofilm: recent approaches - Anmol Kulshrestha; Pratima Gupta (Folia Microbiologica, 2023)

Physical mapping of the wheat genes in low-recombination regions: radiation hybrid mapping of the C-locus - Anmol Kajla; Adam Schoen; Carl Paulson; Inderjit Singh Yadav; Kumari Neelam; Oscar Riera-Lizarazu; Jeff Leonard; Bikram S. Gill; Prakash Venglat; Raju Datla; Jesse Poland; Gary Coleman; et al. (Theoretical and Applied Genetics, 2023)

Destruction and defluorination of PFAS matrix in continuous-flow supercritical water oxidation reactor: Effect of operating temperature - Conrad Austin; Jianna Li; Stuart Moore; Anmol Purohit; Brian R. Pinkard; Igor V. Novosselov (Chemosphere, 2023)

Change in environmental justice scores in historically redlined communities compared to non-redlined communities: A case study of Richmond, Virginia - Anmol Mital (Urban Climate, 2023)

Destruction of PFAS in AFFF-impacted fire training pit water, with a continuous hydrothermal alkaline treatment reactor - Brian R. Pinkard; Conrad Austin; Anmol L. Purohit; Jianna Li; Igor V. Novosselov (Chemosphere, 2023)

Successive addition of rice straw biochar enhances carbon accumulation in soil irrigated with saline or non-saline water - Manpreet Singh Mavi; Gurpreet Singh; Om Parkash Choudhary; Anmol Singh; Bharat Bhushan Vashisht; Karamjit Singh Sekhon; Neemisha Pathania; Bhupinderpal Singh (Environmental Research, 2023)

Methylene blue removal using raw and modified biomass Plumeria alba (white frangipani) in batch mode: isotherm, kinetics, and thermodynamic studies - Jahnabi Deka; Hitesh Das; Anmol Singh; Pranjit Barman; Arundhuti Devi; Krishna G. Bhattacharyya (Environmental Monitoring and Assessment, 2023)

Structural Profiles of SARS-CoV-2 Variants in India - Soumyananda Chakraborti; Jasmita Gill; Ritu Goswami; Sanjeev Kumar; Anmol Chandele; Amit Sharma (Current Microbiology, 2023)

Dietary intervention with Tinospora cordifolia improved aging-related decline in locomotor coordination and cerebellar cell survival and plasticity in female rats - Anmol Bhandari; Shikha Kalotra; Payal Bajaj; Aditya Sunkaria; Gurcharan Kaur (Biogerontology, 2022)

Accumulation of biomedical waste during the COVID-19 pandemic: concerns and strategies for effective treatment - Pon Pavithiran Kuppusamy; Arpit Bhatia; Anmol Verma; Nehal Ratnesh Shah; Prakash Pratyush; Vigneswaran Shanmugarajan; Sung Chul Kim; GaneshKumar Poongavanam; Sakthivadivel Duraisamy (Environmental Science and Pollution Research, 2022)

Aging-related changes in metabolic indicators in female rats and their management with Tinospora cordifolia - Anmol Bhandari; Ashwani Kumar Sharma; Harpal Singh; Amritpal Singh; Gurcharan Kaur (Biogerontology, 2022)

Giant (30 km-diameter) silicic caldera of K/Pg boundary age in the northwestern Deccan Traps: the Alech Hills, Saurashtra - Hetu Sheth; Anmol Naik; Janisar M. Sheikh; Alok Kumar (International Journal of Earth Sciences, 2022)

An Integrated Approach of the Potential Underlying Molecular Mechanistic Paradigms of SARS-CoV-2-Mediated Coagulopathy - Anmol Goyal; Rajendra Prasad; Parul Goel; Amit Pal; Suvarna Prasad; Isha Rani (Indian Journal of Clinical Biochemistry, 2021)

Experimental Investigation on CNT-Enhanced Neopentyl glycol Solid–Solid PCM for Applications of Thermal Control in Spatial Remote Sensing Instruments - Cyril Reuben Raj; S. Suresh; Vivek Kumar Singh; R. R. Bhavsar; Anmol Panda (Journal of the Indian Society of Remote Sensing, 2021)

Diverse late-stage (≤ 62.5 Ma) Deccan volcanism and plutonism in the Thane–Vasai region, Panvel flexure zone, western Indian rifted margin - Anmol Naik; Janisar M Sheikh; Hetu Sheth; Hrishikesh Samant; Shawn D’Souza (Journal of Earth System Science, 2021)

Chikungunya-specific IgG and neutralizing antibody responses in natural infection of Chikungunya virus in children from India - Anil Verma; Kaustuv Nayak; Anmol Chandele; Mohit Singla; Vinod H. Ratageri; Rakesh Lodha; Sushil Kumar Kabra; Kaja Murali-Krishna; Pratima Ray (Archives of Virology, 2021)

Widespread rheomorphic and lava-like silicic ignimbrites overlying flood basalts in the northwestern and northern Deccan Traps - Janisar M. Sheikh; Hetu Sheth; Anmol Naik; Tanmay Keluskar (Bulletin of Volcanology, 2020)

Adverse effects of aminoglycosides in children with drug resistant tuberculosis - Ira Shah; Anmol Goyal; Naman S. Shetty (Infectious Diseases, 2019)

Enhanced Neuronal Survival and Neurite Outgrowth Triggered by Novel Small Organic Compounds Mimicking the LewisX Glycan - Thomas Theis; Anmol Singh Johal; Maciej Kabat; Sayantani Basak; Melitta Schachner (Molecular Neurobiology, 2018)

Childhood multi-drug resistant tuberculosis with paradoxical granulomas – role of steroids - Ira Shah; Anmol Goyal (Infectious Diseases, 2016)